ENSURING SUSTAINABLE ECONOMIC GROWTH OF LIVESTOCK PRODUCTION ENTERPRISES: RISKS, DIRECT AND INDIRECT LOSSES (Development Service Industry Management, 2025)
The article is devoted to the study of risk management and ensuring the sustainability of economic growth of livestock production enterprises in an unstable external environment.It is established that ensuring sustainable economic growth of livestock production enterprises is a complex task that constantly faces numerous risks that can lead to significant direct and indirect losses.It is determined that direct losses include deterioration of animal health, reduced productivity, increased production costs, loss of livestock, and destruction of infrastructure (as was the case with granaries). Indirect losses include loss of consumer confidence, changes in market conditions, reduced investment attractiveness, and reputational losses.It is proven that military actions, as in the case of Ukraine, are a vivid example of a catastrophic external factor destabilizing the industry. Energy supply issues, such as the lack of electricity for crop storage, demonstrate vulnerability to infrastructure and logistical challenges.It is argued that enterprises need to constantly adapt to changing conditions to ensure sustainable economic growth. This requires the development and implementation of effective risk management strategies, investment in modern technologies, diversification of supply sources, and development of reserve capacities.The results of the Global Food Security Index (GFSI) are analyzed. Ukraine's low ranking highlights systemic problems and the need for a comprehensive approach to ensuring food security at the national level.In general, to ensure the sustainability of economic growth of livestock production enterprises in the face of constant challenges, it is extremely important to implement a comprehensive approach to risk management, combining enterprises' internal reserves with effective state support and investments in innovation.
Keywords: geopolitical tensions; economic growth; direct and indirect losses; livestock producers; food security; risks; resilience; risk management